2022
DOI: 10.1111/nph.18068
|View full text |Cite
|
Sign up to set email alerts
|

A MITE variation‐associated heat‐inducible isoform of a heat‐shock factor confers heat tolerance through regulation of JASMONATE ZIM‐DOMAIN genes in rice

Abstract: High temperatures cause huge yield losses in rice. Heat-shock factors (Hsfs) are key transcription factors which regulate the expression of heat stress-responsive genes, but natural variation in and functional characterization of Hsfs have seldom been reported.A significant heat response locus was detected via a genome-wide association study (GWAS) using green leaf area as an indicative trait. A miniature inverted-repeat transposable element (MITE) in the promoter of a candidate gene, HTG3 (heat-tolerance gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…Warm temperature has also been shown to increase levels of 12HSO 4 -JA and consequently alter levels of bioactive JA-Ile; this leads to the stabilization of JAZ proteins, which in turn facilitates plant growth (Zhu et al, 2021). In tomato and rice, HT also inhibits JA accumulation (Pan et al, 2019;, with the rice protein OsHTG3 conferring heat tolerance through activating expression of two JAZ genes (Wu et al, 2022). Exogenous application of JA has proved effective in improving plant stress tolerance under adverse temperature conditions, whether low or high (Du et al, 2013;Pan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Warm temperature has also been shown to increase levels of 12HSO 4 -JA and consequently alter levels of bioactive JA-Ile; this leads to the stabilization of JAZ proteins, which in turn facilitates plant growth (Zhu et al, 2021). In tomato and rice, HT also inhibits JA accumulation (Pan et al, 2019;, with the rice protein OsHTG3 conferring heat tolerance through activating expression of two JAZ genes (Wu et al, 2022). Exogenous application of JA has proved effective in improving plant stress tolerance under adverse temperature conditions, whether low or high (Du et al, 2013;Pan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Conserved roles of the HSFA-mediated JA pathway in regulating anthocyanin biosynthesis under HT in Arabidopsis and tea Numerous studies have reported that JA participates in the heat stress response; however, its specific physiological role in heat response remains ambiguous in plants (Pan et al, 2019;Wu et al, 2022). Here, we applied the same JA-related treatments described above in tea plants (MeJA, ibuprofen, or MeJA + MG132) to Arabidopsis in order to explore the conserved roles of JA in plant HSR.…”
Section: Csjaz6 Represses Catechin Biosynthesis Though Physically Int...mentioning
confidence: 99%
“…Current evidence suggests that siRNA-triggered TE methylation tends to cause the repression of neighboring genes (Hollister and Gaut, 2009; Hollister et al, 2011). However, in the case of MITEs, both positive and negative effects on the expression of host genes have been reported (Gagliardi et al ., 2019; Underwood et al ., 2022; Wu et al ., 2022; Xu et al ., 2020; Zhang et al ., 2016). The weak correlation between methylation of MITEs and the expression of adjacent genes can now be better explained in the light of our findings showing that IRs located near genes affect the local chromatin organization.…”
Section: Discussionmentioning
confidence: 99%
“…Many TE-derived inverted repeated (IR) insertions may not be classified as MITE as they lack the above-mentioned components of MITEs, either due to deletions after insertion, or because they were generated through a different process. MITEs are commonly situated near coding genes: for example, almost 60% of rice genes can be associated with a MITE (Lu et al ., 2012), with the MITEs often changing the expression of neighboring genes (Lu et al ., 2012; Underwood et al, 2022; Wu et al, 2022; Xu et al, 2020; Zhang et al, 2016). Based on this, MITEs have been proposed to play important roles in genome evolution and gene expression (Lu et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Jasmonic acid (JA) and its methyl ester play important roles in plant responses to biotic and abiotic stresses. HEAT-TOLERANCE GENE ON CHROMOSOME 3 (HTG3) regulates thermotolerance in rice by upregulating two heat-responsive JASMONATE ZIM-DOMAIN (JAZ) genes (Wu et al, 2022a). Auxin plays an important role in maintaining spikelet fertility, and decreased levels of the active auxin indole-3-acetic acid (IAA) can cause pollen abortion.…”
Section: Heat Stress and Phytohormonesmentioning
confidence: 99%